Pengaruh Struktur Modal dan Profitabilitas Terhadap Kualitas Laba PT. Unilever Indonesia TBK Periode 2019-2023 - Irma Handayani; Deri Apriadi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This study aims to determine how much the effect of capital structure and profitability on earnings quality at PT Unilever Indonesia Tbk for the 2019-2023 period using secondary data accessed through www.unilever.co.id with a sampling method using purposive sampling technique. The data analysis method is quantitative analysis using descriptive statistics. The results showed that Capital Structure partially had no effect on Earnings Quality. This result is obtained from the t test results on the Capital Structure variable showing a significance level of 0.066 and a t value of 1.967 < t table 2.10982. Meanwhile, Profitability partially affects Earnings Quality. This result is obtained from the t test results on the Profitability variable showing a significant level of 0.009 and a calculated t value of 2.967 < t table 2.10982. The effect of Capital Structure and Profitability simultaneously / together on Earnings Quality at PT. Unilever Indonesia Tbk 2019-2023 where based on the F test, the calculated f value is 8.979 with a significance value of 0.002. While f table 3.55. Then f count is greater than f table.